Efficiency of prenatal diagnosis in Pierre Robin sequence. (26th October 2017) - Di Pasquo, Elvira; Amiel, Jeanne; Roth, Philippe; Malan, Valérie; Lind, Katia; Chalouhi, Christel; Soupre, Véronique; Gordon, Christopher T.; Lyonnet, Stanislas; Salomon, Laurent J.; Abadie, Véronique
Abstract: Objectives: To analyze the efficiency of prenatal diagnosis of Pierre Robin sequence (PRS) regarding the final specific diagnosis and to determine whether infants have more severe respiratory disorders with than without prenatally suspected PRS. Methods: Review of the outcome of all prenatal cases of suspected PRS managed in our prenatal diagnosis center during the last 15 years; analysis of the consistency between prenatal and postnatal diagnoses in 2 groups of women with and without a family history of PRS; comparison of the grades of disease severity for infants with and without prenatally suspected PRS. Results: Fifty‐nine files were studied. Prenatal and postnatal consistencies of a specific diagnosis of PRS were 100% for women with a family history of PRS and with prenatally suspected nonisolated PRS. It was 78.6% for those with prenatally suspected isolated PRS. We describe 13 terminations of pregnancy. The 41 children living beyond 18 months seem to have more functionally severe phenotypes than the 227 children without prenatally suspected PRS. Conclusion: Prenatal diagnosis of isolated PRS is a challenge as other features can be missed. Use of prenatal chromosomal microarray can improve the accuracy of diagnosis. In all cases, adequate neonatal care should be offered. Abstract : What's already known about this topic? Prenatal detection of retrognathia is improving with good fetal imaging but remains nonspecific, which implies many diagnoses with various prognoses. What does this study add? Prenatal diagnosis of PRS is efficient in familial cases and in nonisolated PRS, but prenatal diagnosis of isolated PRS fails in 1/5 of cases, which leads to challenging prenatal counseling. Prenatally suspected PRS may lead to severe neonatal respiratory disorders necessitating birth management in adapted conditions.